Federal Enterprice Architecture Framework Pada Sistem Ujian Sekolah Studi Kasus MTS Al-Hibsiyah - Lestari, Linda; Saepudin, Sudin (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The rapid development of information technology has brought changes to almost all aspects of human life, especially activities in the world of education. One of the vital things in the world of education is the final school exam which is always held at the end of each semester. The process of the School Final Examination or UAS which is carried out manually in this school has several shortcomings and problems. The main problem is the matter of school fees and expenses when carrying out UAS. This is due to the increase in the price of stationery and the number of new students entering. The design of this system is nothing but to help reduce expenses caused by the ATK costs which continue to increase every year. This design uses FEAF as a research model. The FEAF model is a conceptual model that formulates organizational goals and visions in a documented manner and has a coordinated structure between business lines between departments. Business, information needed to support business, technology to support business operations, and the process of moving from old technology to new technology can be done with this framework.